A Genome-Wide Association Study Identifies Candidate Genes Associated With Shell Color in Bay Scallop Argopecten irradians irradians - Zhu, Xinghai; Zhang, Junhao; Hou, Xiujiang; Liu, Pingping; Lv, Jia; Xing, Qiang; Huang, Xiaoting; Hu, Jingjie; Bao, Zhenmin (Frontiers in Marine Science, 2021)
Molluscan shell color has consistently drawn attention for its abundant diversity and commercial use in shellfish breeding projects. Recently, two new strains of bay scallop (Argopecten irradians irradians) with different shell colors as marked phenotypic traits have been artificially bred to improve their economic values; however, the inheritance mechanism of their shell pigmentation is still unclear. In this study, a genome-wide association study (GWAS) was conducted to determine the genetic basis of shell color in bay scallops utilizing 29,036 high-quality single-nucleotide polymorphisms (SNPs) derived from 80 purple-red (PP) and 80 black-brown (BP) shell color individuals. The result of the GWAS showed that 469 SNPs (p <1.72E−6) significantly associated with shell color were mainly distributed in chromosome 7. The top three SNPs (i.e., chr7-12764003, chr7-13213864, and chr7-11899306) are located in the genic region of G-protein-coupled receptor-like 101 (GRL101), polyketide synthase 1 (PKS1), and phosphoinositide phospholipase C (PLC1), which have been widely reported to be involved in pigmentation. Successfully, the top three SNPs were verified in another non-breeding bay scallop population. Furthermore, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses obtained 38 GO terms covering 297 genes and aggregating pathways involving 252 annotated genes. Specifically, the expression profiles of the top three identified candidate genes were detected in mantles of PP and BP individuals by real-time quantitative reverse transcription PCR. The significantly higher expression levels of GRL101 (6.43-fold) and PLC1 (6.48-fold) in PP, and PKS1 (12.02-fold) in BP implied that GRL101 and PLC1 potentially functioned in PP shell coloration, and black pigmentation in BP might be principally regulated by PKS1. Our data provide valuable information for deciphering the phenotype differences of shell color in the bay scallop.